Management Of Bovine Cutaneous Papillomatosis With Ivermectin In Farm Bred Calf Crops Of West Bengal - Jana, Debasis; Mukherjee , Samir Kr. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Incidence of infectious bovine cutaneous papillomatosis in farm bred calf crops of tropical West Bengal during 2008-2010 and its successful therapeutic management, with injectable Ivermectin is reported. Effects of parenteral Ivermectin administration @ 1ml/50 kg body wt. by S/C route in three consecutive doses at 15 days interval were clinically evaluated on 36 calves. Hundred per cent clinical recovery (n : 36) was observed in treatment group whereas persistence as well as different stages of papillomatous growth without regression or self cure was observed in (n : 10) control group.
Keywords: Bovine papillomatosis; Warts; Ivermectin; Calves